Digitising the Deserted Medieval Villages Archive of the Austrian Society for Medieval and Modern Archaeology: The ‘DeVill’ Project - Filzwieser, Roland; Scharrer-Liška, Gabriele; Eichert, Stefan; Kühtreiber, Thomas; Kühtreiber, Karin; Huber, Jacqueline; Siegmeth, Nora (Medieval Settlement Research, 2024)
The DeVill project, initiated by the Austrian Society for Medieval and Modern Archaeology, aims to digitise its extensive archive of deserted medieval villages (DMVs), previously managed and significantly contributed to by Kurt Bors, and to make it online accessible. Since its inception in the early 1970s, the archive has grown to encompass a wealth of information, including literature, written sources, cartographic materials, and archaeological findings, primarily about the Federal States of Lower Austria, Burgenland, and Styria. The digitisation effort, catalysed by the challenges of accessing the physical archive and spurred by a grant funded by the state of Austria and the EU, utilises OpenAtlas with a backend structured around CIDOC-CRM to facilitate interdisciplinary research and public engagement. DeVill aims to provide comprehensive online access to these resources, offering detailed site views, digital terrain models, and an interactive map of DMVs, thereby enhancing both academic research and local historical interest.